Fungsi Aizuchi Sebagai Strategi Kesantunan Dalam Anime “Apothecary Diaries” Season 1 Karya Natsu Hyuga - Cahya Aura Prameshwari; Putu Dewi Merlyna Yuda Pramesti; I Wayan Sadyana (Civiliza Publishing, Indonesia., 2026)
In Japanese communication, aizuchi plays an important role in maintaining interaction and expressing attentiveness toward the speaker. Although aizuchi has been widely studied as a listener response, its role as a politeness strategy in fictional conversations remains underexplored. This study aims to analyze the forms, types, and functions of aizuchi that reflect politeness strategies in the anime